Detection of Chloramphenicol Residues in Pigs with Different Agar Diffusion Methods - Korkeala, Hannu (Acta Vet Scand, 1984)
Various tissues and body fluids of pigs given chloramphenicol intramuscularly at a dose level of 20 mg/kg 1.5, 2.5 and 18 h before slaughter were examined for drug residues with different agar diffusion methods. Zones of inhibition were observed in bile, kidney, muscle, serum and urine samples 1.5 h after drug administration. After 19 h, residues were found only in the urine. The treatment of the bile, kidney, serum and urine samples with β-glucuronidase lowered the detection threshold of the agar diffusion methods for chloramphenicol. In addition, β-glucuronidase can be used for the identification of chloramphenicol residues. Chloramphenicol yielded the greatest zones of inhibition in kidney medulla and especially in urine with and without β-glucuronidase. 18 h after drug administration residues were found with β-glucuronidase treatment only in these samples. Urine and kidney medulla proved the best samples in the residue analysis of chloramphenicol at meat inspection.